Modulation of Gut Microbiota by Magnesium Isoglycyrrhizinate Mediates Enhancement of Intestinal Barrier Function and Amelioration of Methotrexate-Induced Liver Injury - Xia, Yawen; Shi, Hang; Qian, Cheng; Han, Hongkuan; Lu, Keqin; Tao, Ruizhi; Gu, Renjun; Zhao, Yang; Wei, Zhonghong; Lu, Yin (Frontiers in Immunology, 2022)
Background The gut–liver axis plays a crucial role in various liver diseases. Therefore, targeting this crosstalk may provide a new treatment strategy for liver diseases. However, the exact mechanism underlying this crosstalk and its impact on drug-induced liver injury (DILI) requires clarification. Aim This study aimed to investigate the potential mechanism and therapeutic effect of MgIG on MTX-induced liver injury, which is associated with the gut–liver axis and gut microbiota. Methods An MTX-induced liver injury model was generated after 20-mg/kg/3d MTX application for 30 days. Meanwhile, the treatment group was treated with 40-mg/kg MgIG daily. Histological examination, aminotransferase, and aspartate aminotransferase enzyme levels were estimated to evaluate liver function. Immune cells infiltration and inflammatory cytokines were detected to indicate inflammation levels. Colon histological score, intestinal barrier leakage, and expression of tight junctions were employed to assess the intestinal injury. Bacterial translocation was observed using fluorescent in situ hybridisation, colony-forming unit counting, and lipopolysaccharide detection. Alterations in gut microbial composition were analysed using 16s rDNA sequencing and relative quantitative polymerase chain reaction. Short-chain-fatty-acids and lactic acid concentrations were then utilized to validate changes in metabolites of specific bacteria. Lactobacillus sp. supplement and fecal microbiota transplantation were used to evaluate gut microbiota contribution. Results MTX-induced intestinal and liver injuries were significantly alleviated using MgIG treatment. Bacterial translocation resulting from the intestinal barrier disruption was considered a crucial cause of MTX-induced liver injury and the therapeutic target of MgIG. Moreover, MgIG was speculated to have changed the gut microbial composition by up-regulating probiotic Lactobacillus and down-regulating Muribaculaceae, thereby remodelling the intestinal barrier and inhibiting bacterial translocation. Conclusion The MTX-induced intestinal barrier was protected owing to MgIG administration, which reshaped the gut microbial composition and inhibited bacterial translocation into the liver, thus attenuating MTX-related DILI.